A NEW SPECIES OF DIPLYCOSIA (ERICACEAE) FROM SOUTH KALIMANTAN, INDONESIA - Wilkie, P.; Argent, G. C. G. (Edinburgh Journal of Botany, 2016)
A new species, Diplycosia kalimantanensis P.Wilkie & Argent (Ericaceae), collected on an expedition to Gunung Besar in the Meratus mountains, South Kalimantan, is described and illustrated, and a conservation assessment provided.